G459(P) Improving the investigation of unexpected infant deaths. (27th April 2015) - Garstang, J; Ellis, C; Griffiths, F; Sidebotham, P
Abstract : Aims: Since 2008, in England, all unexpected infant deaths must be investigated jointly by police, health and social services. This study aims to learn of bereaved parents' and professionals' experiences of this joint agency approach (JAA) as well as assess the effectiveness of the JAA in determining causes and risk factors for deaths and use this knowledge to improve professional practice. Methods: A mixed methods study of JAA investigation of SUDI cases in one English region; involving case note analysis, questionnaires and in–depth interviews with bereaved parents and the relevant professionals. A descriptive study of outcomes of JAA SUDI investigation using Child Death Overview Panel (CDOP) data. Results: 23/111 families were recruited giving theoretical saturation. The median time between infants' deaths and parental study participation was 33 weeks; data collection took place between 2011–3. 25 professionals were interviewed. CDOP Form Cs were obtained for 65/70 (93%) SUDI cases dying during 2010–2. Non–specialist police often arrived at the parents' home along with the ambulance; increasing parental distress. Parents felt that the JAA provided information about why their baby died but offered minimal emotional support. The joint home visit by police and paediatrician is a key investigative process and most parents found this helpful. Final case discussions were used to discuss relevant risk factors but not to determine the cause of death; in nearly all cases the final cause of death relied on post–mortem examination alone ignoring findings of death scene examinations. Many deaths fitted the diagnostic criteria for SIDS but despite this were labelled as unascertained. Social care were only involved in 13/23 JAA investigations, in two cases without involvement there were safeguarding concerns. Some Coroners were reluctant to share post–mortem examination reports with paediatricians preventing effective JAA investigations. Conclusion: Ideally, SUDI investigations should be carried out only by specialist clinicians who do this work frequently and the JAA fully integrated with social care and Coroners' investigations. There needs to be a clearer system for classifying unexplained SUDI. Police should reconsider their immediate response to SUDI; parents would like more follow–up and bereavement support from professionals.